Adangiyah - Bambang Sunarto (Pascasarjana Institut Seni Indonesia Surakarta, 2021)
This edition is the first issue of Dewa Ruci’s Journal, in which all articles are in English. We deliberately changed the language of publication to English to facilitate information delivery to a wider audience. We realize that English is the official language for many countries rather than other languages in this world. The number of people who have literacy awareness and need scientific information about visual and performing arts regarding the archipelago’s cultural arts is also quite large.The decision to change the language of publication to English does not mean that we do not have nationalism or are not in love with the Indonesian language. This change is necessary to foster the intensity of scientific interaction among writers who are not limited to Indonesia’s territory alone. We desire that the scientific ideas outlined in Dewa Ruci’s Journal are read by intellectual circles of the arts internationally. We also want to express our scientific greetings to art experts from countries in New Zealand, the USA, Australia, Europe, especially Britain, and other English-speaking countries such as the Philippines, India, Pakistan, Zimbabwe, the Caribbean, Hong Kong, South Africa, and Canada. Of course, a change in English will also benefit intellectuals from countries that have acquired English as a second language, such as Malaysia, Brunei, Israel, Malaysia, and Sri Lanka. In essence, Dewa Ruci’s Journal editor wants to invite writers to greet the scientific community at large.We are grateful that six writers can greet the international community through their articles. The first is Tunjung Atmadi and Ika Yuni Purnama, who wrote an article entitled “Material Ergonomics on Application of Wooden Floors in the Interior of the Workspace Office.” This article discusses office interiors that are devoted to workspaces. The purpose of this study is to share knowledge about how to take advantage of space-forming elements in the interior design of a workspace by utilizing wooden floors like parquet. The focus is on choosing the use of wood by paying attention to the elements in its application. This research result has a significant meaning in the aesthetics, comfort, and safety of wooden floors in the workspace’s interior and its advantages and disadvantages.The second writer who had the opportunity to greet the Dewa Ruci Journal audience was intellectuals with diverse expertise, namely Taufiq Akbar, Dendi Pratama, Sarwanto, and Sunardi. Together they wrote an article entitled “Visual Adaptation: From Comics to Superhero Creation of Wayang.” This article discusses the fusion and mixing of wayang as a traditional culture with comics and films as contemporary culture products. This melting and mixing have given birth to new wayang creations with sources adapted from the superhero character “Avenger,” which they now call the Avenger Wayang Kreasi. According to them, Wayang Kreasi Avenger’s making maintains technical knowledge of the art of wayang kulit. It introduces young people who are not familiar with wayang kulit about the technique of carving sungging by displaying the attributes in the purwa skin for Wayang Kreasi Avenger. This creativity is an attempt to stimulate and show people’s love for the potential influence of traditional cultural heritage and its interaction with the potential of contemporary culture.The next authors are Sriyadi and RM Pramutomo, with an article entitled “Presentation Style of Bedhaya Bedhah Madiun Dance in Pura Mangkunegaran.” This article reveals a repertoire of Yogyakarta-style dance in Mangkunegaran, Surakarta, namely the Bedhaya Bedhah Madiun. The presence of this dance in Mangkunegaran occurred during the reign of Mangkunegara VII. However, the basic character of the Mangkunegaran style dance has a significant difference from the Yogyakarta style. This paper aims to examine the Bedhaya Bedhah Madiun dance’s presentation style in Mangkunegaran to determine the formation of its presentation technique. The shape of the Bedhaya Bedhah Madiun dance style in Mangkunegaran did not occur in an event but was a process. The presentation style’s formation is due to a problem in the inheritance system that has undergone significant changes. These problems arise from social, political, cultural, and economic conditions. The responses to these problems have shaped the Bedhaya Bedhah Madiun dance's distinctive features in Mangkunegaran, although not all of them have been positive.Hasbi wrote an article entitled “Sappo: Sulapa Eppa Walasuji as the Ideas of Creation Three Dimensional Painting.” This article reveals Hasbi’s creative process design in creating three-dimensional works of art, named Sappo. He got his inspiration from the ancient manuscripts written in Lontara, namely the manuscripts written in the traditional script of the Bugis-Makassar people on palm leaves, which they still keep until now. Sappo for the Bugis community is a fence that limits (surrounds, isolates) the land and houses. Sappo’s function is to protect herself, her family, and her people. Sulapa Eppa means four sides, is a mystical manifestation, the classical belief of the Bugis-Makassar people, which symbolizes the composition of the universe, wind-fire-water-earth. Walasuji is a kind of bamboo fence in rhombus rituals. Eppa Walasuji’s Sulapa is Hasbi’s concept in creating Sappo in the form of three-dimensional paintings. The idea is a symbolic expression borrowing the Lontara tradition's idiom to create a symbolic effect called Sappo.Mahdi Bahar and his friends wrote an article entitled “Transformation of Krinok to Bungo Krinok Music: The Innovation Certainty and Digital-Virtual Contribution for Cultural Advancement.” Together, they have made innovations to preserve Krinok music, one of Jambi’s traditional music themes, into new music that they call Bungo Krinok. He said that innovation is a necessity for the development of folk music. In innovating, they take advantage of digital technology. They realize this music’s existence as a cultural wealth that has great potential for developing and advancing art. The musical system, melodic contours, musical grammar, and distinctive interval patterns have formed krinok music’s character. This innovation has given birth to new music as a transformation from Jambi folk music called “Bungo Krinok” music.Finally, Luqman Wahyudi and Sri Hesti Heriwati. They both wrote an article entitled “Social Criticism About the 2019 Election Campaign on the Comic Strip Gump n Hell.” They explained that in 2019 there was an interesting phenomenon regarding the use of comic strips as a means of social criticism, especially in the Indonesian Presidential Election Campaign. The title of the comic is Gump n Hell by Errik Irwan Wibowo. The comic strip was published and viral on social media, describing the political events that took place. In this study, they took three samples of the comic strip Gump n Hell related to the moment of the 2019 election to analyze their meaning. From the results of this study, there is an implicit meaning in the comic strip of pop culture icons' use to represent political figures in the form of parodies.That is the essence of the issue of Volume 16 Number 1 (April Edition), 2021. Hopefully, the knowledge that has been present in this publication can spur the growth of visual and performing art science in international networks, both in the science of art creation and in scientific research of art in general. We hope that the development of visual and performing art science can reveal the various meanings behind various facts and phenomena of art life. Therefore, the growth of international networks is an indispensable need.Thank you.